Adequacy of the application of the concept of "moral damage" to legal entities - Kirichenko , T. (Київський національний університет імені Тараса Шевченка, 2019)
The article is devoted to the study of the application of the concept of moral harm to legal entities, taking into account the artificial nature of their occurrence, as well as the need to protect the personal non-property rights of these participants in legal relations.

Стаття присвячена дослідженню застосування поняття моральної шкоди до юридичних осіб, враховуючи штучну природу їх виникнення, а також необхідність захисту особистих немайнових прав цих учасників правовідносин.
Адекватність застосування поняття «моральна шкода» до юридичних осіб
Keywords: legal entity; personal non-property rights; moral harm; business reputation of the legal entity; юридична особа; особисті немайнові права; моральна шкода; ділова репутація юридичної особи.